Physico-Chemical Analysis of Fresh and Fermented Fruit Juices Probioticated with Lactobacillus casei - Kumar, Bathal Vijaya; Sreedharamurthy, Mannepula; Reddy, Obulam Vijaya Sarathi (International Journal of Applied Sciences and Biotechnology, 2013)
The objective of this study was to find out the suitability of different fruit juices for probiotication by using Lactobacillus casei. Phyto-chemical analysis of different fruit juices (mango, sapota, grape and cantaloupe) were carried out using the standard methods. Carbohydrates, flavoniods, tannins, glycosides were present and alkaloids and saponins were absent in all the above fruit juices. Further analysis by TLC and DPPH methods indicated good antioxidant activity in all the fruit juices except for cantaloupe juice. Probiotication of fruit juices with L. casei, decreased pH and increased the titratable acidity within 72 h. Physico-chemical properties were also determined at different time intervals (24, 48 and 72 h) of probiotication. Based on the above results, it was inferred that the beverage prepared from the probiotication of fruit juices with L. casei could be useful in providing health benefits to the consumers. DOI: http://dx.doi.org/10.3126/ijasbt.v1i3.8301 Int J Appl Sci Biotechnol, Vol. 1(3) 2013 : 127-131